(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Breast cancer is one of the most common cancers worldwide. Breast cancer screening modalities help in reducing the morbidity and mortality associated with the disease. Objective: This study aimed at assessing knowledge and awareness of breast cancer risk factors and screening methods amongst undergraduate pharmacy students of Ahmadu Bello University (ABU) Zaria, Nigeria. Methods: The study was carried out on 235 conveniently sampled fourth- and fifth-year undergraduate pharmacy students. Data was collected through a self-administered questionnaire that assessed the students’ knowledge and awareness of breast cancer risk factors, breast self-examination (BSE), clinical breast examination (CBE) and mammography. Each correct response was scored one (1) point and each wrong response was scored zero (0). Respondents with scores 0–2 were considered to have poor knowledge, those with 3-5 points had fair knowledge while those with 6-8 points had good knowledge. SPSS was used to analyze the data, knowledge was described by frequencies and percentages while chi-square test was used to compare responses between 400 and 500 level students, p<0.05 was considered significant in all the analyses. Results: Of the 228 students that participated in the study, 69 (30.3%) were fourth year students while the remaining 159 (69.7%) were fifth year students. Mean age of the participants was 24±3.14. Majority were males 139 (61%) and single 210 (92.1%). Knowledge and awareness scores were; good 24 (10.5%), fair 137 (60.1%), poor 67 (29.4%) for breast cancer risk factors, good 96 (42.1%), fair 90 (39.5%), poor 42 (18.4%) for BSE, good 16 (7%), fair 144 (63.2%), poor 68 (29.8%) for CBE and good 5 (2.2%), fair 165 (72.4%), poor 58 (25.4%) for mammography respectively. When the scores were compared between the levels, a significant difference was obtained (p< 0.0001) for knowledge and awareness of BSE. Conclusion: The study revealed a fair level of knowledge and awareness of breast cancer risk factors and screening methods amongst undergraduate pharmacy students of ABU Zaria.